PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI BAGIAN UMUM RSUD MAJALAYA - Bayu Framesthi, Dyah; Sudrajat, Ade (Jurnal Ilmiah Magister Ilmu Administrasi, 2024)
A good working environment is crucial, especially in the context of hospitals, where the quality of services and employee productivity directly affect the health and well-being of patients. This research aims to test the influence of the working environment (X) on the productivity of the work of the staff (Y) in the General Division of RSUD Majalaya district of Bandung. Data in this research is obtained by conducting the dissemination of the questionnaire on the staff who are in the Public Division, so that the data in this study is primary data. The population in this study is the whole employee in the General Division, with sampling in this research is the entire population on the study object. The results of the analysis show that the working environment has a significant influence on employee productivity. Improving the working environment will increase employee productivity.